2005
DOI: 10.1111/j.1460-9568.2005.04162.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the GLT‐1 subtype of glutamate transporter in glutamate homeostasis: the GLT‐1‐preferring inhibitor WAY‐855 produces marginal neurotoxicity in the rat hippocampus

Abstract: Glutamate is the major excitatory neurotransmitter in the central nervous system and is tightly regulated by cell surface transporters to avoid increases in concentration and associated neurotoxicity. Selective blockers of glutamate transporter subtypes are sparse and so knock-out animals and antisense techniques have been used to study their specific roles. Here we used WAY-855, a GLT-1-preferring blocker, to assess the role of GLT-1 in rat hippocampus. GLT-1 was the most abundant transporter in the hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 53 publications
0
24
0
1
Order By: Relevance
“…Methodological differences in the study by Bonde et al (2003), such as the use of serum-free medium during slice maturation and the presence of PI from the very beginning of the experiment, might explain the discrepancy. Previous data actually support the possibility that EAATs can still take up Glu even under ischemic conditions (Rao et al, 2001;Mitani and Tanaka, 2003;Selkirk et al, 2005). It has also been reported that the function of GLT1 may change from neuroprotective (uptake mode) to neurodegenerative (release mode) depending on ischemic conditions (Mitani and Tanaka, 2003).…”
Section: Discussionmentioning
confidence: 64%
“…Methodological differences in the study by Bonde et al (2003), such as the use of serum-free medium during slice maturation and the presence of PI from the very beginning of the experiment, might explain the discrepancy. Previous data actually support the possibility that EAATs can still take up Glu even under ischemic conditions (Rao et al, 2001;Mitani and Tanaka, 2003;Selkirk et al, 2005). It has also been reported that the function of GLT1 may change from neuroprotective (uptake mode) to neurodegenerative (release mode) depending on ischemic conditions (Mitani and Tanaka, 2003).…”
Section: Discussionmentioning
confidence: 64%
“…In a series of experiments, Bonde and colleagues have shown that blocking glutamate transporters with TBOA under normal conditions in rat hippocampal slice cultures results in marked necrotic neurodegeneration, presumably due to increased glutamate in the synaptic cleft, as the effect is blocked by glutamate receptor antagonists [238]. In addition, TBOA exacerbates ischemia in rat hippocampus [239].…”
Section: Disease Conditions Associated With Alterations In Excitatorymentioning
confidence: 98%
“…In principle, this seems likely because glutamate uptake is already expressed in the neonatal brain and readily demonstrated even in primary cultures (Danbolt, 2001). In addition, TBOA neurotoxicity is reported to occur when this agent is bath-applied to neuronal cultures from neonatal animals as much as when it is microinjected into the rat adult brain in vivo (Selkirk et al 2005), indicating a widespread potential for neurotoxicity when glutamate uptake is blocked.…”
Section: Correlation Between Bursting and Excitotoxicitymentioning
confidence: 99%